Enhancing Literacy through Technology: How U-Dictionary Supports Reading Skills Development in English Learners - Rasyidah, Ummi; Triana, Novita; Rizky, Ramanda (JOLLT Journal of Languages and Language Teaching, 2025)
As technology becomes an integral part of education, the use of mobile apps offers interactive learning opportunities that go beyond traditional classroom methods. Therefore, this study explores the impact of the U-Dictionary app in improving English Reading Skills among senior high school students at SMAN 1 Rambah. A quasi-experimental design was used, involving an experimental group that used the U-Dictionary app and a control group that followed conventional reading practices. Pretest and posttest assessments were conducted to measure the improvement in reading Skills. The data were analyzed using descriptive statistics and an independent sample t-test via SPSS 25. The findings show a statistically significant improvement in the experimental group (p < 0.05), with a moderate effect size, indicating that the U-Dictionary application has a positive impact on studentsâ€™ Reading Skills and it enhance motivation and academic achievement. The findings highlight U-Dictionary’s interactive features, which offer immediate feedback and facilitate vocabulary acquisition, making the learning process engaging. The study concludes by recommending the incorporation of such technologies in language curricula to create dynamic learning environments that prepare students for future academic and professional challenges. The results of this study advocate the adoption of technology-enhanced strategies in educational settings to foster better learning outcomes.